Nurses’ information management at patients’ discharge from hospital to home care - Ragnhild Hellesø; Lena Sorensen; Margarethe Lorensen (International Journal of Integrated Care, 2005)
Purpose: The purpose of this paper is to explore and compare hospital and home care nurses’ assessment of their information management at patients’ discharge from hospital to home care before and after the hospital implemented an electronic nursing discharge note. Theory: This paper draws on the concept of inter-organizational continuity of care, and specifically addresses the contribution of the implementation of an electronic patient record (EPR). Methods: The study has a prospective descriptive design. A questionnaire addressing the information that hospital and home care nurses exchange when patients need continuing care after hospitalization was developed and used. Results: Hospital and home care nurses differed in the way they assessed the structures and content of the information they exchanged, both before and after the EPR implementation. Conclusion and discussion: There is a need to take account of the different organizational contexts within which the two nursing groups work. The organizational context (hospital versus home care) has implications for the nurses’ assessment of the information they exchange. In further development of EPR, it is therefore essential to clarify the context-related information needs of the various health care provider groups as part of the commitment to patient safety.